Malaysian fruit bats phylogeny inferred using ribosomal RNA - Jeffrine Japning Rovie-Ryan; Andy Kho Han Guan; Jayaraj V.K; Abdullah M.T (2008)
Fourteen species of the Malaysian fruit bats (Pteropodidae) were used in this DNA taxaonomy using 1,334bp of the 125 ribosomal RNA (rRNA), transfer RNA (tRNA) valine and 16S rRNA gene segments. Previous studies using DNA found contradictious between morphology and molecular data in inferring the phylogeny of the fruit bat proposed by Audersen (1912). Our phylogenetic analysis using the neighbor-joining and the maximum parsimony methods did not support the monophyly of subfamily Macroglossinae and the cynopterine group of the subfamily Pteropodinae as proposed by classical taxouomist. This is cougruent with previous molecular studies. Here, we provide the first registered 12S rRNA, tRNA valine and 16S rRNA sequence records for Dyacopterus spadiceus in the GenBank database. This study represents the first attempt to infer the phylogeuetic relationship of fruits bats from Malaysia using molecular methods